Instilling Social Care Character in Children Aged 4–5 Years Through the IHF 9 Character Pillars Book - Sri Indahyani; Kartika Rinakit Adhe; Wulan Patria Saroinsong; Nurul Istiq’faroh; Andi Kristanto; Sayhidul Haq (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Character education in early childhood is a critical foundation for developing prosocial behavior, particularly helping behavior as part of social-emotional development. Specific Background In Indonesian early childhood education settings, many children aged 4–5 years still demonstrate low initiative in sharing, cooperating, and assisting peers, partly due to the absence of structured and systematic learning media. Knowledge Gap Although the Indonesia Heritage Foundation (IHF) 9 Character Pillars Book is widely recognized in practice, empirical studies focusing on its use as a single, structured medium to instill the value of helping others remain limited. Aims This study aims to analyze the implementation process and outcomes of using the IHF 9 Character Pillars Book to cultivate helping behavior among Group A children aged 4–5 years in a formal early childhood education context. Results Using a descriptive qualitative case study approach at RA Al-Falah Tuban, the findings indicate that staged implementation of the IHF book—integrated into daily learning activities—was associated with observable improvements in children’s willingness to help, share, and participate in cooperative tasks, with the proportion of children demonstrating spontaneous helping behavior increasing from initial observations to the end of the intervention period. Novelty This study provides in-depth evidence on the use of a standardized character education book as a focused medium for instilling helping values in early childhood. Implications The findings offer a practical, structured model for teachers to integrate story-based character education into routine classroom practices, while highlighting the importance of consistency between school and home environments.Highlights: Staged classroom integration of character storybooks supported observable growth in children’s prosocial actions. Teacher-guided reflection and role play facilitated the internalization of care and cooperation values. Consistency between educational settings and home practices emerged as a key supporting condition. Keywords: Early Childhood Education, Character Education, Helping Behavior, IHF 9 Character Pillars, Storybook Media